The impact of environmental pH on the gut microbiota community structure and short chain fatty acid production. Issue 5 (6th April 2022) - Firrman, Jenni; Liu, LinShu; Mahalak, Karley; Tanes, Ceylan; Bittinger, Kyle; Tu, Vincent; Bobokalonov, Jamshed; Mattei, Lisa; Zhang, Huanjia; Van den Abbeele, Pieter
Abstract: Environmental pH is a critical parameter for maintenance of the gut microbiota. Here, the impact of pH on the gut microbiota luminal and mucosal community structure and short chain fatty acid (SCFA) production was evaluated i n vitro, and data compiled to reveal a donor-independent response to an increase or decrease in environmental pH. The results found that raising environmental pH significantly increased luminal community richness and decreased mucosal community evenness. This corresponded with an increased abundance of Ruminococcaceae Ruminococcus and Erysipelotrichaceae Erysipelatoclostridium, and a decreased abundance of Coriobacteriaceae Collinsella and Enterobacteriaceae Shigella for both the luminal and mucosal communities. Total SCFA levels were significantly higher, primarily due to an increase in acetic and 2-methylbutanoic acids. Lowering pH decreased luminal community evenness and decreased mucosal community evenness and richness. This corresponded with an increased abundance of Lachnospiraceae Enterocloster, Veillonellaceae Megasphaera, Veillonellaceae Sporomusa, Erysipelotrichaceae Eubacterium, and Alcaligenaceae Sutterella, and decreased abundance of Odoribacteraceae Butyricimonas, Fusobacteriaceae Fusobacterium, Veillonellaceae Phascolarctobacterium, and multiple Enterobacteriaceae species for both the luminal and mucosal communities. Total SCFA levels were significantly lower, with an observed drop in acetic and propionic acids, and increased butyric and valeric acids. Taken together, these results indicate that alterations to environmental pH can modulate the gut microbiota community structure and function, and some changes may occur in a donor-independent manner. Abstract : Changes to environmental pH alter the gut microbiota structure and function in vitro .